2019
DOI: 10.1242/jcs.232819
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization of the land-plant-specific microtubule nucleation factor MACET4

Abstract: Here, we show that the embryophyte (land-plant)-specific protein MACERATOR4 (MACET4) binds microtubules in vitro and in vivo, promotes microtubule polymerization at sub-critical tubulin concentrations, decreases the lag phase in microtubule bulk polymerization assays, and colocalizes with microtubule nucleation sites. Furthermore, we find that MACET4 forms oligomers that induce aster formation in vitro in a manner that is similar to aster formation mediated by centrosomes and TPX2. MACET4 is expressed during c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 56 publications
(71 reference statements)
1
12
0
Order By: Relevance
“…This study's findings are an important addition to understanding microtubule organization mechanisms in plant cells, as are those from a recent independent study by Schmidt and Smertenko [7], which identified the same Arabidopsis protein as MACERATOR4. BLAST searches so far indicate that CORD4/ MACET4 is specific to the plant lineage, whereas other known phragmoplast components are highly conserved across eukaryotic taxa.…”
supporting
confidence: 56%
“…This study's findings are an important addition to understanding microtubule organization mechanisms in plant cells, as are those from a recent independent study by Schmidt and Smertenko [7], which identified the same Arabidopsis protein as MACERATOR4. BLAST searches so far indicate that CORD4/ MACET4 is specific to the plant lineage, whereas other known phragmoplast components are highly conserved across eukaryotic taxa.…”
supporting
confidence: 56%
“…Mutations in other class 12 Kinesins, such as A. thaliana PAKRP1 and PAKRP2 (Kinesins 12A and 12B) and P. patens KINID1a and KINID1b (Kinesins 12B) lead to severe phragmoplast structural defects not seen in pok or o1 , despite similar localization to the phragmoplast (Lee et al, 2007; Pan et al, 2004; Hiwatashi et al, 2008). Indeed, mutations in several phragmoplast-localized proteins result in defects that alter phragmoplast structure, often leading to cell wall stubs and multinucleate cells (Bannigan et al, 2007; Ho et al, 2011; Schmidt and Smertenko, 2019; Zhang et al, 2018, 3; Müller et al, 2004). The similar phenotypes of pok and o1 coupled with their physical interaction suggests they work together to ensure correct phragmoplast guidance.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to the use of the motor-only construct with which we could not recapitulate the plus end enrichment of Kinesin-13. Alternatively, considering the decrease and increase in catastrophe and rescue frequency of interphase MTs, it is possible the Kinesin-13 regulates the growth and shrinkage rate indirectly via tubulin cycling: reduced catastrophe would result in reduced availability of tubulin in the free tubulin pool, which might affect MT growth and shrinkage rates, as was proposed in studies of Arabidopsis Armadillo Repeatcontaining Kinesin (ARK) proteins (Eng and Wasteneys, 2014) and more recently for the plant-specific MT nucleator MACERA-TOR4 (MACET4; Schmidt and Smertenko, 2019).…”
Section: Discussionmentioning
confidence: 99%